Visual Stereotypes of Tatars in the Finnish Press from the 1880s to the 1910s - Elmgren, Ainur (Studia Orientalia Electronica, 2020)
Visual stereotypes constitute a set of tropes through which the Other is described and depicted to an audience, who perhaps never will encounter the individuals that those tropes purport to represent. Upon the arrival of Muslim Tatar traders in Finland in the late nineteenth century, newspapers and satirical journals utilized visual stereotypes to identify the new arrivals and draw demarcation lines between them and what was considered “Finnish”. The Tatars arrived during a time of tension in the relationship between the autonomous Grand Duchy of Finland and the Russian Empire, with the Finnish intelligentsia divided along political and language lines. Stereotypical images of Tatar pedlars were used as insults against political opponents within Finland and as covert criticism of the policies of the Russian Empire. Stereotypes about ethnic and religious minorities like the Tatars fulfilled a political need for substitute enemy images; after Finland became independent in 1917, these visual stereotypes almost disappeared.